2007
DOI: 10.4315/0362-028x-70.8.1917
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Self-Reported Behaviors and Cognitions of Young Adults: Results of a National Study

Abstract: With limited opportunities to learn safe food handling via observation, many young adults lack the knowledge needed to keep them safe from foodborne disease. It is important to reach young adults with food safety education because of their current and future roles as caregivers. With a nationwide online survey, the demographic characteristics, self-reported food handling and consumption behaviors, food safety beliefs, locus of control, self-efficacy, stage of change, and knowledge of young adults with educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
126
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 46 publications
22
126
3
1
Order By: Relevance
“…Such differences are consistent with previous findings in the United States (e.g. Byrd-Bredbenner et al, 2007a) and in Europe (Sanlier and Konaklioglu, 2012), and are also found for food hygiene behaviours such as hand-washing (Anderson et al, 2008). Males may therefore be at greater risk of foodborne illness than females, and future interventions should be designed accordingly to target male populations.…”
Section: Predictors Of Knowledge Scoressupporting
confidence: 90%
See 1 more Smart Citation
“…Such differences are consistent with previous findings in the United States (e.g. Byrd-Bredbenner et al, 2007a) and in Europe (Sanlier and Konaklioglu, 2012), and are also found for food hygiene behaviours such as hand-washing (Anderson et al, 2008). Males may therefore be at greater risk of foodborne illness than females, and future interventions should be designed accordingly to target male populations.…”
Section: Predictors Of Knowledge Scoressupporting
confidence: 90%
“…Studies conducted on adults have indicated that food safety knowledge tends to increase with age and practice (Byrd-Bredbenner et al, 2007a). Females tend to have higher scores than males in food safety knowledge, and younger consumers (under 19 years old) show the most inappropriate practices and significantly lower food hygiene knowledge.…”
Section: The Role Of Knowledgementioning
confidence: 99%
“…As a consequence, food-safety objectives are now being set at the moment of consumption rather than at the moment of purchase (WHO/FAO, 2004) with consumers being heralded as the essential final link in the food chain to ensure safe food consumption and avoid food-borne disease (The Pennington Group, 1997, as cited in Redmond et al, 2004). This shift in focus has allowed researchers to comprehensively examine domestic food preparation practices using telephone surveys (Cody & Hogue, 2003;Redmond & Griffith, 2004a;Woodburn & Raab, 1997), postal surveys (Angell, 2008;Dharod et al, 2004;Redmond & Griffith, 2005a;Redmond & Griffith, 2005b;Redmond & Griffith, 2006a;Takeuchi et al, 2005a;Takeuchi et al, 2005b;Williamson et al, 1992), online surveys (Byrd-Bredbenner et al, 2007;Nauta et al, 2008;Unusan, 2007), home visits (Worsfold & Griffith, 1996), observations (Anderson et al, 2004;Clayton et al, 2003;Fischer, A. et al, 2007;Jay et al, 1999;Redmond & Griffith, 2006b;Redmond et al, 2004), laboratory simulations (Meredith et al, 2001) and reviews (Redmond & Griffith, 2003;Sattar et al, 1999;Wilcock et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study assessing knowledge of food safety in ϳ4000 young adults showed that participants were only able to answer 60% of the questionnaire correctly and had trouble designating foods with higher food safety concerns. 16 Although our study did not measure knowledge of food storage practices, only 50% of parents attempted to provide cold storage with ice packs for their preschool-aged children's sack lunches. Safe practices and relationships between food handling and personal health need to be taught and reinforced.…”
Section: Discussionmentioning
confidence: 99%